Semantics and Linguocultural Characteristics of Some Uzbek Lexemes - Kadirova Barno Raimovna (Researchparks Publishing, 2022)
At a time when international relations are developing and interaction is intensifying, the study of languages and cultures of different nations remains one of the urgent tasks. By the end of the twentieth century, linguistics had assumed that